Circular RNAs Are Regulators of Diverse Animal Transcriptomes: One Health Perspective - Zucko, Dora; Boris-Lawrie, Kathleen (Frontiers in Genetics, 2020)
Derived from linear (parental) pre-mRNA, circRNA are recycled exons and introns whose ends are ligated. By titrating microRNAs and RNA binding proteins, circRNA interconnect networks of competing endogenous RNAs. Without altering chromosomal DNA, circRNA regulates skeletal muscle development and proliferation, lactation, ovulation, brain development, and responses to infections and metabolic stress. This review integrates emerging knowledge of circRNA activity coming from genome-wide characterizations in many clades of animals. CircRNA research addresses one of the main pillars of the One Health vision - to improve the health and productivity of food animals and generate translational knowledge in animal species.